Evaluation of lumbar core stability among club level cricket bowlers: a cross-sectional study - Hafsa; Sabahat Butt; Amna Imran; Moazzam Ali; Zara Khalid; Hafiz Ali Bin Asim (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the lumbar core stability in club-level cricket bowlers. Method: The descriptive cross-sectional study was conducted in the twin cities of Rawalpindi and Islamabad in Pakistan from July 15 to December 10, 2022, after approval from the ethics review board Foundation University Medical College, Islamabad, and comprised male, club-level, hard-ball cricket bowlers aged 18-24 years. Data was collected through a self-structured demographic sheet, and core stability was assessed using McGill Torso Muscle Endurance Test Battery. Data was analysed using SPSS 21. Results: There were 296 male subjects with a mean age of 20.1±1.77 years. Of them, 90(30.4%) bowlers had good lumbar flexion-to-extension ratio and 206(69.6%) had poor ratio. Lateral endurance test of right-to-left side-bridge ratio showed 71(24%) players in the good category, and 225(76%) in the poor category. The ratio of right lateral endurance to lumbar extensor was good in 55(18.6%) and poor in 241(81.4%) subjects. The ratio of left lateral endurance to lumbar extensor endurance was good in 40(13.5%) players and poor in 256(86.5%). Conclusion: Lumbar core stability was found to be quite poor among club-level cricket bowlers of Rawalpindi and Islamabad. Key Words: Athletes, Core stability, Cricket, Bowlers, Sport.